Dynamics of Consumer Boycotts: Exploring the Interplay of Expressive and Instrumental Factors - Robertus Suraji; Marrisa Haque; Yasir, Muhammad; Istianingsih, Istianingsih (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2023)
This research explores consumer participation in product boycotts in Indonesia, focusing on the interplay between expressive and instrumental factors over time. Through a systematic literature review, this study reveals that emotional responses and personal identity trigger boycotts, serving as expressions of solidarity or protests against conflicting values. As time progresses, practical considerations, such as boycott effectiveness, become dominant motivators, following the